Chinese Higher Education: “Glass Ceiling” and “Feet of Clay” - Altbach, Philip G (International Higher Education, 2016)
China has seen remarkable academic growth and also improvement in the quality of its top universities. However, problems remain at the top of the higher education system in terms of overbureaucratization and other issues. The bottom “mass-based” institutions have been largely ignored in terms of their financing and quality.